Effectiveness and safety of dual influenza and pneumococcal vaccination versus separate administration or no vaccination in older adults: a meta-analysis. (3rd July 2018) - Yin, Mingjuan; Huang, Lingfeng; Zhang, Yan; Yu, Na; Xu, Xiaojia; Liang, Yaping; Ni, Jindong
ABSTRACT: Background: The advantages of dual pneumococcal and influenza vaccination in older adults have not been clarified and controversy remains regarding their optimal use. Methods: This meta-analysis was conducted on 25 January 2018 using PubMed, the Cochrane Library, and Embase databases. Seventeen studies were selected ultimately for meta-analysis using a multi-step approach by two separate authors. Primary outcomes were pneumonia, pneumococcal pneumonia, influenza, hospitalization, and all-cause mortality rates, and the secondary outcome was adverse effects (AEs). Results: The additive preventive effects of dual inﬂuenza and pneumococcal vaccination versus inﬂuenza vaccination alone for pneumonia and death were 15% (95% confidence interval [CI]: 4-24%) and 19% (95% CI: 6-30%), respectively. Compared with pneumococcal vaccination alone, dual influenza and pneumococcal vaccination resulted in a 24% (95% CI: 16-31%) reduction in pneumonia and a 28% (95% CI: 13-40%) reduction in death. Compared with placebo or no vaccination, the effectiveness of dual vaccination was 29% (95% CI: 14-42%) for pneumonia, 38% (95% CI: 25-49%) for death, 35% (95% CI: 22-46%) for influenza, and 18% (95% CI: 6-29%) for hospitalization. Both vaccines showed acceptable safety profiles and AEs were mild or moderate. Conclusion: Our findings highlight the importance of concomitant influenza and pneumococcal vaccination in older adults.